The Influence of Brand Awareness, Brand Image, Product Quality, and Price on Purchasing Decisions on Eucalyptus Oil Products UD. Rejeki Jaya - Revina A. Wilar; Aileen Chandra; Christianna Purnamasari; Monalisa (Accounting Profession Journal (APAJI), 2025)
This research investigates the influence of brand awareness, brand image, product quality, and price on consumer purchasing decisions in the context of UD. Rejeki Jaya, a traditional medicine MSME that specializes in eucalyptus oil. A quantitative approach was used, with primary data collected from 53 respondents through a structured questionnaire. Data were analyzed using descriptive statistics, correlation, and regression analysis to identify relationships and test hypotheses. The data analysis technique was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) approach using WarpPLS version 6.0 software, to identify the significant influence of each variable. The research results show that brand awareness, brand image, product quality and price have a significant influence on purchasing decisions. This study contributes to existing knowledge by emphasizing the important role of brand awareness in MSMEs operating in niche markets. This study offers practical implications, including strategies for improving branding efforts, maintaining product quality, and optimizing prices to holistically meet consumer needs.